Pengaruh Budaya Organisasi, Work Engagement Terhadap Komitmen Dan Kinerja Karyawan Pada Perusahaan Pelayaran Di Semarang - Adenanthera Lesmana Dewa; Lisda Rahmasari (Universitas 45 Surabaya, 2023)
The purpose of this study to analyze the effect of organization culture (X1), work engagement (X2) to organization commitment (Y1) and employee performance (Y2). In this study, data were collected through questionnaires to 90 respondents to determine the response of respondents to each variable. Then analyze the data obtained in the form of quantitative analysis and qualitative analysis. Quantitative analysis include validity and reliability test, the classic assumption test, hypothesis testing via the F test and t test and analysis test, the coefficient of determination (R2). Data analysis techniques used were linear regression analysis that serves to prove the research hypothesis. The data that have met the test validity, test reliability, and classical assumption processed so as to produce the following regression equation: Y1= 0.244X1 + 0.467X2 and Y2 = 0,202X1 + 0,394X2 + 0,209X3 . Results of the analysis found that organization culture (X1), work engagement (X2) has a positive and significant influence on organization commitment (Y1) and organization culture (X1), work engagement (X2) , organization commitment (X3) has a positive and significant influence on employee performance (Y2) . Hypothesis testing using t test showed that independent variables found to significantly affect dependent variables.